Homogeneous Li deposition through the control of carbon dot-assisted Li-dendrite morphology for high-performance Li-metal batteries. Issue 35 (22nd August 2019) - Hong, Dongki; Choi, Yuri; Ryu, Jaegeon; Mun, Jinhong; Choi, Wooyeong; Park, Minju; Lee, Yongwon; Choi, Nam-Soon; Lee, Geunsik; Kim, Byeong-Su; Park, Soojin
Abstract : The synergistic interplay between surface negative charges and functional groups in the carbon dot establish a strong Li-ion affinity, resulting in homogeneous Li deposition. Abstract : Lithium metal as a battery anode is one of the most promising energy storage materials owing to its high theoretical capacity and low working potential. However, uncontrollable Li growth during cycling raises safety issues in the battery due to dendrite formation and a poor coulombic reversibility. Here, a design involving carbon nanodots (CDs) as electrolyte additives is introduced, which could significantly improve the morphology of the Li plating and cycling stability of lithium-metal batteries (LMBs). These CDs are suitable electrolyte additives because they show good dispersibility against organic solvents, originating from their 2–5 nm small-sized particles. In addition, CDs include surface negative charges and various functional groups, which are easily controllable through modulating the amount and types of precursors used. The surface negative charges and the functional groups in the CDs draw Li cations by electrostatic force and provide a strong Li-ion affinity. This synergistic combination enables uniform Li-ion transportation to the current collector, resulting in metal reduction with a smooth surface during the plating/stripping process. Moreover, the control of the CD-assisted Li dendrite morphology was examined by ex situ transmission electron microscopy. In the LMB full-cell tests with limited 20 μm-thick Li metal, the CD-containing electrolytes exhibited a capacity retention value of 99.9% after 100 cycles. Here, the CD-assisted Li deposition minimized the risks originating from Li dendrite growth, thus stabilizing the cycling ability of the LMB.